Idahoa and Subularia: Hidden polyploid origins of two enigmatic genera of crucifers - Dogan, Mert; Mandáková, Terezie; Guo, Xinyi; Lysak, Martin A (American journal of botany, 2022)
PREMISE: The monotypic Idahoa (I. scapigera) and the bispecific Subularia (S. aquatica and S. monticola) belong to Brassicaceae with unclear phylogenetic relationships and no tribal assignment. To fill this knowledge gap, we investigated these species and their closest relatives by combining cytogenomic and phylogenomic methods. METHODS: We used whole plastome sequences in maximum likelihood and Bayesian inference analyses. We tested the phylogenetic informativeness of shared genomic repeats. We combined nuclear gene tree reconciliation and comparative chromosome painting (CCP) to examine the occurrence of past whole-genome duplications (WGDs). RESULTS: The plastid data set corroborated the sister relationship between Idahoa and Subularia within the crucifer Lineage V but failed to resolve consistent topologies using both inference methods. The shared repetitive sequences provided conflicting pwhylogenetic signals. CCP analysis unexpectedly revealed that Idahoa (2n = 16) has a diploidized mesotetraploid genome, whereas two Subularia species (2n = 28 and 30) have diploidized mesoctoploid genomes. Several ancient allopolyploidy events have also been detected in closely related taxa (Chamira circaeoides, Cremolobeae, Eudemeae, and Notothlaspideae). CONCLUSIONS: Our results suggest that the contentious phylogenetic placement of Idahoa and Subularia is best explained by two WGDs involving one or more shared parental genomes. The newly identified mesopolyploid genomes highlight the challenges of studying plant clades with complex polyploidy histories and provide a better framework for understanding genome evolution in the crucifer family.
Keywords: molekulární evoluce; Polyploidy; plastome phylogeny; Bayes Theorem; Brassicaceae; mesopolyploidy; Lineage V; repeatome; Subularieae; Cruciferae; Bayesova věta; Hyb-Seq; Genome; fylogeneze; genom; CES clade; whole-genome duplication; Phylogeny; polyploidie; Evolution, Molecular